Casein kinases as potential therapeutic targets. (3rd March 2016) - Cozza, Giorgio; Pinna, Lorenzo A
Abstract : Introduction: The conventional term 'casein kinase' (CK) denotes three classes of kinases – CK1, CK2 and Golgi-CK (G-CK)/Fam20C (family with sequence similarity 20, member C) – sharing the ability to phoshorylate casein in vitro, but otherwise unrelated to each other. All CKs have been reported to be implicated in human diseases, and reviews individually dealing with the druggability of CK1 and CK2 are available. Our aim is to provide a comparative analysis of the three classes of CKs as therapeutic targets. Areas covered: CK2 is the CK for which implication in neoplasia is best documented, with the survival of cancer cells often relying on its overexpression. An ample variety of cell-permeable CK2 inhibitors have been developed, with a couple of these now in clinical trials. Isoform-specific CK1 inhibitors that are expected to play a beneficial role in oncology and neurodegeneration have been also developed. In contrast, the pathogenic potential of G-CK/Fam20C is caused by its loss of function. Activators of Fam20C, notably sphingolipids and their analogs, may prove beneficial in this respect. Expert opinion: Optimization of CK2 and CK1 inhibitors will prove useful to develop new therapeutic strategies for treating cancer and neurodegenerative disorders, while the design of potent activators of G-CK/Fam20C will provide a new tool in the fields of bio-mineralization and hypophosphatemic diseases.